(untitled) (Al-Aasar, 2025)
This article looks at the ethical Hadith derived guidelines to help Muslims staying in non Muslim societies regarding how they should maintain their religious identities while trying to live in peace and integration. The teachings of the Prophet Muhammad (PBUH) provide a sociological model for social behavior, religious tolerance, political engagement and economic ethics which provide Muslims with a moral compass in multicultural environments. Nevertheless, Muslims living in non Muslim society are subjected to enormous problems such as cultural disparities, legal conflict, social pressure and generational barrier. As there are cultural norms which may not align with Islamic teachings, legal systems that do not accommodate religious practice and the general Islamophobia, Muslims attempting to balance being Muslim with the societal expectations present unique obstacles. Furthermore, generational differences in the way in which the Islamic teachings are interpreted and applied make integration more complicated. While these challenges exist, Muslim leaders and scholars are very important to help guide communities through these issues without losing sight of their faith. Educational programs and interfaith dialogue initiatives such as these are the key to bridging gaps between Muslims and non Muslims. If Muslims stick to the Islamic ethical principles of justice, honesty and compassion, they can make positive contributions to their host societies, while maintaining their religious identity. The purpose of this article is to show the need for ethical behavior, community participation, and dialogue in creating a harmonious multicultural community. In the end, the Muslim experience in non Muslim societies shows us the necessity of adaptation, resilience, as well as an ethics attached to them, a global world that can accommodate faith and integration.